Level of satisfaction with the quality of instruction CM-UPV students - Barrameda, Kelly; Bulao, Jenny Mae; De Mesa, Charlene Heart; Flores, Maria Reyna; Gadong, Diana Joy; Naces, Patricia Marie
The study was conducted to find out the level of satisfaction of the CM-UPV students with the quality of instruction when grouped according to their year level, course and general weighted average. The Stratified Random Sampling was used to obtain the 76 respondents from the College of Management-University of the Philippines Visayas where the respondents were given a structured questionnaire, which consists of four parts. The first part asking for the respondent's socio-demographic profile, the second part which consists of questions on quality of instruction, the third part on teaching methods and the fourth part on instructional facilities. The data obtained was encoded and then analyzed using SPSS for Windows software version 14.0. The results showed that majority of the respondents are "satisfied" with the level of instruction of the CM-UPV faculty. Also, when they are grouped according to year level, course and general weighted aaverage, results still show that the respondents are satisfied. Further, there exists no significant difference in the level of satisfaction of the respondents when the respondents were grouped according to their course and general weighted average. This means that the level of satisfaction of students were more or less the same, that is, satisfied. On the other hand, there is a significant difference existed in the level of satisfaction of the CM-UPV students when the respondents were classified according to their year level which means that the level of satisfaction of the student varies.